New optimal analysis method to stability and H∞ performance of varying delayed systems. (October 2019) - Qian, Wei; Xing, Weiwei; Wang, Lei; Li, Bingfeng
Abstract: This work investigates the stability and H ∞ performance of interval time-varying delay systems. The aim is to find new optimal analysis method, which can integrate the constructed Lyapunov–Krasovskii functional (LKF) with estimating technique effectively to reduce the conservatism of the main results. A new augmented vector and LKF with triple integral terms are constructed to establish relationships among different vectors firstly. Then two different integral inequalities are used to show how to integrate constructed LKF with estimating technique effectively to reduce the conservatism of the main criteria. Meanwhile, less conservative criteria are derived compared with some existing results. Numerical examples are also given to show the superiority of the proposed approaches.